MANAGEMENT OF DESTRUCTIVE SIGN-OUT CELEBRATIONS IN NIGERIAN TERTIARY INSTITUTIONS - Iwuagwu, Judith Nkechi; Nwokonko Roberta Nwadiuto (Proceeding of International Conference on Social Science and Humanity, 2026)
Objective: This paper examined the growing menace of sign-out celebrations in Nigerian tertiary institutions and discussed strategies that institutional managers can adopt to address the problem. Method: The study adopted a review-based method through the examination of existing literature, newspaper reports, institutional observations, and documented incidents relating to sign-out practices in higher institutions. Results: The paper identified weak institutional regulations, moral decline, peer influence, inadequate counselling services, and poor security monitoring as major factors encouraging the trend. The study concluded that if urgent administrative and moral interventions are not introduced, the culture of destructive sign-out celebrations may continue to undermine the core values and integrity of tertiary education in Nigeria. Novelty: The paper recommended the establishment of clear institutional policies, strengthening of counselling services, provision of structured celebration alternatives, improvement in campus security, and active student participation in behavioural reorientation programmes.